Effect of Different Local Vibration Durations on Knee Extensors’ Maximal Isometric Strength - Nicolas Amiez; Stella Zografou; Tom Timbert; Alain Martin; Spyridon Methenitis; Nicolas Babault; Christos Paizis (Applied Sciences, 2023)
The prolonged application (>20 min) of local vibration (LV) on muscles or tendons is known to reduce maximal isometric strength. However, the effect of short vibration durations (≤6 min) is still unknown. In fourteen participants, the changes in maximal voluntary isometric contraction (MVIC) were measured after 1, 3, and 6 min of rest (CONT) or local vibration (LV) over the quadricipital tendon (frequency: 100 Hz; amplitude: 0.5 mm). Before and after each condition, the amplitude of the twitch induced by a 100 Hz potentiated electrical doublet (PDPOT); the relative electromyographic activity of the vastus medialis and rectus femoris muscle during the MVIC (RMSMVIC.M−1); the torque developed 50 ms after the onset of contraction (T50); and the voluntary activation level (VAL) were evaluated. None of the three LV durations significantly changed the MVIC compared with the control condition (p = 0.379). The indices of central (i.e., VAL, T50, RMSMVIC.M−1) and peripheral (e.g., PDPOT) fatigue were unaffected (p > 0.147). In conclusion, a short-duration LV (≤6 min) on a voluminous muscle group does not impair maximal force production or induce any central or peripherical fatigue.